Investigation the effect of the alcoholic extract of Zingiber officinale on liver enzymes and oxidative stress during ischemia reperfusion injury - Mohammed, Mustafa T. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Hepatic ischemia-reperfusion (I/R) injury may occur in a variety of clinical settings and this remains a significant problem. Oxygen free radicals, produced on reperfusion have been shown to play a major role in hepatic I/R injury. Various therapeutic effects have been described for Zingiber officinale. Additionally, it has been presented that Zingiber officinale has protective effect against ischemia reperfusion injury to various organs. Therefore, it seems possible that the administration of Zingiber officinale might protect the liver against the ischemia reperfusion injury. Objectives : To determine whether Zingiber officinale prevents hepatic ischemia-reperfusion injury to the liver. Methods: Thirty-six rats were divided into three groups as control (Group 1), I/R group (Group 2), and Zingiber officinale treatment group (Group 3). All rats underwent hepatic ischemia for 60 min followed by 60 min period of reperfusion. Rats were internalely infused with only 0.9% saline solution in group 2. Rats in group 3 received alcoholic extract of Z. officinale (200 mg/kg) intraperitoneally, before ischemia and before reperfusion. Blood samples were harvested from the rats, and then the rats were sacrificed. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) oxidative stress levels of reactive oxygen species (ROS) ,nitric oxide (NO) and lipid peroxidation (LPO) levels were determined. Results: The levels of liver enzymes and Oxidative stress in group 3 were significantly lower than those in the group 2. Conclusion: Our results suggest that Zingiber officinale treatment protects the rat liver against hepatic ischemia-reperfusion.